Analysis of energy processes in pulse converters of AC electric power - Kadatsky, A. F.; Rusu, A. P. (Technology and design in electronic equipment, 2015)
The article presents the analysis of energy processes in switched-mode AC-AC converters of buck, boost and buck-boost types. The mathematical model of energy processes is obtained. The mathematical model is generalized to DC-DC and AC-AC converters, to three basic types of converters and considers the possibility of autotransformer inclusion of an inductor. It is shown that the use of bidirectional switches allows both DC and AC conversion of electrical energy regardless of the load type, and also supports recuperation of electrical energy back to the source. It is shown that the maximum value of instant power in a load circuit in AC-AC converters exceeds twice the rated value of load power in comparison with DC-DC converters. It is shown that the energy capacity of an inductor in AC-AC converters exceeds twice the energy capacity of DC-DC converters at the identical rated power of conversion. It is shown that the energy capacity of an inductor in converters of buck and boost types depends on the ratio of input and output voltage. Also, the energy capacity of an inductor in converters of buck-boost type does not depend on the ratio of input and output voltage. It is shown that the energy capacity of an inductor in converters of buck and boost types is lower than the energy capacity of an inductor in the converter of buck-boost type.